Adapting the EAT-Lancet diet for West Africa: protein quality and micronutrient inadequacies improved through nutrient dense foods - Sanders, Hannah; Alia, Didier Y.; Lara-Arevalo, Jonathan; Beal, Ty; Drewnowski, Adam (Frontiers in Nutrition, 2026)
BackgroundThe EAT-Lancet planetary health diet was designed as a universal nutritionally adequate diet with minimal environmental impact. We aim to assess and propose revisions to increase its nutrient adequacy in the context of West Africa based on the local food supply.MethodsWe created a model EAT-Lancet diet using nutrient composition data from the FAO's Food Composition Tables for Western Africa (WAFCT). Median energy and nutrient profiles of EAT-Lancet diet food groups were calculated using WAFCT foods (n = 596). Protein content was adjusted using the Protein Digestibility Corrected Amino Acid Score (PDCAAS). We multiplied the recommended EAT-Lancet diet intake for each food subgroup by these medians to determine daily nutrient intake. Nutrient adequacy was determined based on alignment with the FAO Codex nutrient reference values for adults. The Nutrient Rich Food (NRF) index, based on priority micronutrients, defined nutrient density. Isocaloric revisions were made to the EAT-Lancet diet to enhance its nutrient adequacy using WAFCT foods.ResultsTotal energy of the modeled diet was 2,516 kcal/day. Total protein was 87 g/day while PDCAAS corrected protein was 62 g/day. Micronutrient shortfalls were observed for zinc, calcium, and vitamin A but not for iron, folate, and vitamin B12. Increasing intake of nutrient-rich liver, small dried fish, and pulses, while reducing whole grains and tree nuts, achieved micronutrient adequacy.ConclusionWhen analyzed using foods available in West Africa, the EAT-Lancet diet may provide adequate protein but not vitamin A, zinc, and calcium. Future iterations of the diet should consider including categories for micronutrient dense foods to ensure adequacy.